Short Course of Antifungal Therapy in Patients With Uncomplicated Candida Bloodstream Infection: Another Case of Less Is More in the Clinical Setting?. (8th December 2022) - Vena, Antonio; Bovis, Francesca; Tutino, Stefania; Santagostino Barbone, Alessandro; Mezzogori, Laura; Ponzano, Marta; Taramasso, Lucia; Baldi, Federico; Dettori, Silvia; Labate, Laura; Russo, Chiara; Giacobbe, Daniele Roberto; et al.
Abstract: Background: The objective of this study was to compare the clinical outcomes of patients receiving a short course (SC) vs a prolonged course (PC) of antifungal therapy for uncomplicated Candida bloodstream infections (BSIs). Methods: All episodes of uncomplicated Candida BSI from September 1, 2018, to August 31, 2020, were reviewed. We compared the primary (all-cause 90-day mortality) and secondary study end points (1-year recurrent Candida BSI and all-cause 1-year mortality) among patients who underwent SC (5–11 days) or PC (12–24 days) therapy using propensity score analysis with the inverse probability of treatment weighting (IPTW) method. Results: A total of 114 patients with uncomplicated Candida BSI were included: 35 (30.7%) were classified into the SC group (median [interquartile range IQR], 9 [7–11] days) and 79 (69.3%) into the PC group (median [IQR], 14 [14–16] days). Patients in the SC group compared with the PC group had a higher rate of hospitalization in the surgical ward (40.0% vs 19.0%; P = .02) or septic shock at the time of Candida BSI onset (11.4% vs 1.3%; P = .03). The risk of 90-day mortality was not different between the SC and PC groups (n = 8 [22.9%] vs 17 [21.5%], respectively; IPTW-adjusted subdistribution hazard ratio [sHR], 0.67; 95% CI, 0.31–1.47; P = .20). The risk for recurrent Candida BSI within 1 year of completing therapy (IPTW-adjusted sHR, 1.07; 95% CI, 0.20–5.80; P = .94) or for all-cause 1-year mortality (IPTW-adjusted HR, 0.72; 95% CI, 0.35–1.50; P = .38) did not differ between groups. Conclusions: Receiving a short vs prolonged course of antifungal therapy did not affect mortality or BSI recurrence in patients with uncomplicated candidemia.